The endocranial shape of Australopithecus africanus : surface analysis of the endocasts of Sts 5 and Sts 60 - (:unkn) unknown (My University, 2018)
Assessment of global endocranial morphology and regional neuroanatomical changes in early hominins is critical for the reconstruction of evolutionary trajectories of cerebral regions in the human lineage. Early evidence of cortical reorganization in specific local areas (e.g. visual cortex, inferior frontal gyrus) is perceptible in the non-human South African hominin fossil record. However, to date, little information is available regarding potential global changes in the early hominin brain. The introduction of non-invasive imaging techniques opens up new perspectives for the study of hominin brain evolution. In this context, our primary aim in this study is to explore the organization of the Australopithecus africanus endocasts, and highlight the nature and extent of the differences distinguishing A. africanus from the extant hominids at both local and global scales. By means of X-ray-based imaging techniques, we investigate two A. africanus specimens from Sterkfontein Member 4, catalogued as Sts 5 and Sts 60, respectively a complete cranium and a partial cranial endocast. Endocrania were virtually reconstructed and compared by using a landmark-free registration method based on smooth and invertible surface deformation. Both local and global information provided by our deformation-based approach are used to perform statistical analyses and topological mapping of inter-specific variation. Statistical analyses indicate that the endocranial shape of Sts 5 and Sts 60 approximates the Pan condition. Furthermore, our study reveals substantial differences with respect to the extant human condition, particularly in the parietal regions. Compared with Pan, the endocranial shape of the fossil specimens differs in the anterior part of the frontal gyri.
Keywords: African Research